NILAI-NILAI DALAM TRADISI LISAN GENDING MЀMЀJRA DI DESA ADAT SUKAWANA KINTAMANI BANGLI - Murniasih, Ni Luh (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Sukawana Traditional Village as Bali Mula Village has a variety of unique cultures, one of which is oral literature, namely Gending Méméjra. Gending Méméjra is a sacred hymn belonging to the oral tradition. When viewed from the existence of literature in Bali, this gending is included in traditional literature that is sacred, because it functions as an accompaniment to religious ceremonies. As an oral tradition, many do not know the existence of gending, especially this gending is only sung to coincide with the posa ceremony which is held once a year. As a sacred tradition, the existence of gending is used as a guide for the community in living life. There are several values contained in it that should be known by the general public. From this, the purpose of this study is to values contained in each Gending Méméjra lyrics and determine the existence of Gending Méméjra. The results of this study show that Gending Méméjra still exists today, shown by the enthusiasm of the community singing gending. This gending is used as a tool to summon ancestral spirits to come during the posa ceremony and functions as a welcoming song and accompaniment to ancestral spirits present at the posa procession. In addition to storing religious values, this gending also stores social values, cultural preservation, and as a means of maintaining the Balinese language and as wll as being used as medium of entertainmet.